Avaliação técnica e econômica de uma usina teórica de hidrogênio verde fotovoltaica de 1,0 MWe considerando o potencial solar brasileiro - Francisco Edvan Bezerra Feitosa (2024)
Energy is essential for the survival and quality of life of populations and for the economic and social development of nations. However, in recent years, concern about the use of energy resources has become one of the most important problems of collective interest to most nations in the world, for the following reasons: continuous increase in the world population; growing global demand for energy; environmental problems associated with CO2 emissions due to the use of fossil fuels as the main source of energy; the policy responses of some nations are accelerating the emergence of a global economy based on clean energy; the need for a new paradigm capable of maintaining global energy security, reliability and accessibility, and reducing emissions, simultaneously. So, this shows that the need to identify and develop clean and sustainable alternative fuels is becoming increasingly urgent. Among the existing alternatives, green hydrogen stands out, which is being seen as the energy vector of the future, which could replace fossil fuels. The green hydrogen is emerging as a low-carbon fuel option for the transportation, industrial and electrical generation sectors, as it could decarbonize these three large sectors of the world economy. This is explained by the fact that hydrogen has a higher energy content per unit of weight than all fossil fuels, it can be produced only with water and renewable energy, and when used as a fuel it produces only energy and water. Although the consumption of hydrogen as a fuel is not yet widespread, there is growing interest in its use as a potential source of energy, in the so-called hydrogen economy. In this context, this work aimed to simulate and evaluate the production potential of a 1.0 MWe off-grid hydrogen plant powered by photovoltaic energy along the largest Brazilian highway, 4,660 km long, connecting the Northeast Regions, Southeast and South of Brazil. In the end, this work presented: Rankings of the energy production and hydrogen production potential of 23 cities along BR-116; the LCOE – Leveled Cost of Energy and LCOH – Leveled Cost of Hydrogen costs obtained for each of the 23 cities evaluated, using as economic and financial premises, the recommendations of the International Energy Agency for the Group of Twenty (G20). In the end, the work presented ten conclusions and closed by stating that the Northeast Region has a strong vocation for the production of energy and photovoltaic hydrogen, with production of 1,742,078 kWh/year/MW and 27,392 kg of hydrogen/year/MW of installed power, with an average LCOH cost of 4.20 US$/kg.